Determinants of political institutions and their influence on financial inclusion and economic growth - Lacheheb, Zakaria (2020)
This thesis aims to investigate the role of political institution and remittance on economic outcomes, and their influence on financial inclusion and economic growth in developing countries. Notably, political institution is chosen based on the hierarchy of institutional hypothesis (HIH) and it is applied in the three objectives of this thesis. Remittance considers as an important factor of capital flow, due to its stable and huge inflow to developing countries. Remittance has played a pivotal role in poverty alleviation and increasing of recipients’ human capital. For instance, remittance signaled to be a lifeline for millions of recipients that are mostly under poverty, which is a cause of poverty alleviation in emigrants’ countries of origin (Migration Development brief, 2017). The small amounts of $200 or $300 that each migrant sends home make up about 60% of the family’s household income (IFAD, 2017). However, remittance flow parallel with the level of financial inclusion and economic growth in the nations remain in low levels.